Respon Fisiologi Domba pada Sistem Pemeliharaan dan Pemberian Jenis Konsentrat Berbeda - dos Santos, Adelia C. Gonzaga; Yamin, M.; Priyanto, R.; Maheshwari, H. (Jurnal Ilmu Produksi dan Teknologi Hasil Peternakan, 2019)
Sheep is one of the livestock commodities that is developed and utilized by farmer to meet the increasing demand of animal protein. This study aimed to investigate physiological responses of local sheep that were kept on different raising system and given different type concentrate. The study used 24 heads of local sheep with an average initial live weight of 19.79±2.47kg. The experiment was set up in a completely randomized design with two factors. The first factor was rearing system (intensive and semi intensive) and second factor was type of concentrate feed (green and comercial concentrates). The parameters observed were heart rate, rectal temperature, respiration rate, differential leukocytes N/L and cortisol hormone levels. The data were analyzed by repeated mensure analysis of variance (repeted ANOVA). The results showed that the type of concentrate did not affect blood profile and cortisol hormone levels. Sheep’s physiological response (respiration rate, heart rate and rectal temperature) were significantly (P0 <0.5) influenced by rearing system.